Medicina delle complessità e approccio olistico in medicina interna e geriatria. Un modello di integrazione dei servizi - De Michele, Luigi Vincenzo (Il sogno della farfalla, 2025)
This article investigates the relevance and appropriateness of adopting a holistic approach in the management of complex medical conditions such as chronic fatigue syndrome, fibromyalgia, and somatic symptom disorder. It underscores the necessity for coordinated, multidisciplinary care for patients presenting with comorbidities who are caught in a detrimental cycle of disability, which may ultimately lead to functional decline and occupational incapacity. Medical specialties such as rheumatology and orthopedics could substantially benefit from integrating broader perspectives, including insights into mental health disorders. Nonetheless, despite the potential advantages of such integrative approaches, there remains a paucity of robust evidence elucidating the psychodynamic mechanisms underpinning their efficacy, thereby highlighting the need for further empirical research. Additionally, the article examines the success of the Comprehensive Geriatric Assessment in managing frailty among older adults, proposing it as a paradigmatic model for holistic care within contemporary medicine.